(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To assess the success of BMG urethroplasty in long segment anterior urethral stricture. Method: From January 2014 to December 2015, twenty male patients with long anterior segment urethral stricture were managed by BMG urethroplasty. After voiding trial they were followed up at 3 month with Uroflowmetry, RGU & MCU and PVR measurement by USG. Patients were further followed up with Uroflowmetry and PVR at 6 months interval.Successful outcome was defined as normal voiding with a maximum flow rate >15ml /sec and PVR<50 ml with consideration of maximum one attempt of OIU after catheter removal. Results: Mean stricture length was 5.2 cm (range 3-9 cm) and mean follow-up was 15.55 months (range 6-23 months). Only two patients developed stricture at proximal anastomotic site during follow-up. One of them voided normally after single attempt of OIU. Other one required second attempt of OIU and was considered as failure (5%). Conclusion: BMG urethroplasty is a simple technique with good surgical outcome. Bangladesh Journal of Urology, Vol. 19, No. 2, July 2016 p.64-68